2016
DOI: 10.1002/cctc.201600448
|View full text |Cite
|
Sign up to set email alerts
|

Employing a Nickel‐Containing Supramolecular Framework as Ni Precursor for Synthesizing Robust Supported Ni Catalysts for Dry Reforming of Methane

Abstract: This work presents a facile and efficient approach for preparing well dispersed supported Ni catalyst (HMA@Ni/SBA‐15) for dry reforming of methane (DRM) through the modified impregnation method by using a hexamethylenetetramine (HMA) Ni(II) complex, a three‐dimensional hydrogen‐bonded supramolecular framework, as Ni precursor. By employing this method, the NiII cation was discretely impregnated into the mesoporous channels of SBA‐15 support by the “obstacle effect” of the HMA coordination shell of the Ni compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 116 publications
3
8
0
Order By: Relevance
“…Figure a exhibits the results of high-resolution peaks of Ni 2p XPS spectra. The Ni 2p regions contain five easily discernible features for each catalyst: the main peak and its satellite centered at ∼854 and ∼862 eV can be assigned to Ni 2p 3/2 , and the main peak and its satellite located at ∼872, ∼882, and ∼888 eV are attributed to Ni 2p 1/2 , respectively . It is found that the peaks of Ni 2p 3/2 for calcinated Ni/CeO 2 -CAS are weaker than those of Ni/CeO 2 -IWI because of its lower loading, which is consistent with ICP analysis (Table ).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Figure a exhibits the results of high-resolution peaks of Ni 2p XPS spectra. The Ni 2p regions contain five easily discernible features for each catalyst: the main peak and its satellite centered at ∼854 and ∼862 eV can be assigned to Ni 2p 3/2 , and the main peak and its satellite located at ∼872, ∼882, and ∼888 eV are attributed to Ni 2p 1/2 , respectively . It is found that the peaks of Ni 2p 3/2 for calcinated Ni/CeO 2 -CAS are weaker than those of Ni/CeO 2 -IWI because of its lower loading, which is consistent with ICP analysis (Table ).…”
Section: Resultsmentioning
confidence: 68%
“…These supported Ni catalysts are prone to irreversibly suffer from severe sintering problems, via either particle migration-coalescence or Ostwald ripening processes. Hence, the formation of Ni nanoparticles (NPs) with a low dispersity and weak metal–support interaction hinders their long-term use. , It is demonstrated that the highly dispersed supported Ni-based catalysts with strong metal–support interaction (SMSI) play essential roles in catalytic activity for hydrogenation reaction, which are favorable for adsorption of the nitroarenes and dissociation of H 2 molecules as well as acceleration of electron transfer between the metal and the support . Therefore, numerous impregnated strategies were proposed to improve the catalytic performance of supported Ni catalysts, including atomic layer deposition, , microwave-assisted synthesis, and so on. , However, further improvements of Ni dispersion and metal–support interaction for supported Ni catalysts are highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…One approach for controlling the size of the targeted Ni 0 NPs prepared using impregnation techniques is the use of specific nickel precursors. Li et al prepared and utilized a hexamethylenetetramine (HMA) Ni(II) complex (referred to as (NO 3 ) 2 Ni(H 2 O) 6 (HMA) 2 •4H 2 O by the authors), the formation of which could be attested using FTIR spectroscopy (Figure 2), to improve the insertion of Ni into mesoporous support of type SBA-15 (Table 1, entry 13) [40]. (12.7 wt.% of Ni), was synthesized in a similar manner using a nickel nitrate aqueous solution.…”
Section: Use Of Original Nickel Precursors or The Assistance Of Organic Moleculesmentioning
confidence: 99%
“…Generally, activity of a metallic catalyst is determined by the exposure extent of active metal sites . Thus, downsizing the metallic nanoparticles is an ideal strategy for improving their catalytic activity. Besides the notably promoted catalytic activity, designing small-sized metallic NP catalysts has been established as an efficient approach for improving catalytic stability owing to the improved sintering resistance via strong metal–support interaction. Recently, single-atom catalysts, with atomically dispersed metal species on the support surface, have emerged as a new domain for heterogeneous catalysis owing to the maximum atom utilization efficiency, tunable coordination environment, and unique electron structure of active sites. , But, it still has great challenges in efficient synthesis and industrial applications. The tedious procedures and gas release make the synthetic route neither economical nor environmentally benign. , Therefore, the supported metallic NP catalyst still is one of the most potential candidate for practical and industrial applications, and development of facile and efficient strategies for synthesis of supported nanosized metal NP catalysts is still urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The tedious procedures and gas release make the synthetic route neither economical nor environmentally benign. , Therefore, the supported metallic NP catalyst still is one of the most potential candidate for practical and industrial applications, and development of facile and efficient strategies for synthesis of supported nanosized metal NP catalysts is still urgently needed. Till now, the surfactant assisting method, metal complex assisting approach, hetero-aggregation approach, ligand capping, and especially non-noble metal sacrificial approaches have been reported for preparing highly dispersed metal NP catalysts. , However, the high cost and the complex preparation process limit their practical application. It is valuable to develop a facile and practical method for preparing highly dispersed metal NP catalysts.…”
Section: Introductionmentioning
confidence: 99%